2014
DOI: 10.1371/journal.pone.0088042
|View full text |Cite
|
Sign up to set email alerts
|

Association of Schistosoma mansoni-Specific IgG and IgE Antibody Production and Clinical Schistosomiasis Status in a Rural Area of Minas Gerais, Brazil

Abstract: BackgroundStudies in murine models and human populations have indicated that the collagen-rich granulomatous response against parasite eggs trapped in the liver is associated with the development of severe hepatosplenic schistosomiasis, characterized by periportal fibrosis and portal hypertension. The role of the humoral response in parasite susceptibility has been well established, but its participation in disease severity remains poorly understood. In this work, we evaluated the relationship between parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…CXCL10 secretion is under the genetic control of IFN-γ, is up-regulated in Th1-type inflammatory processes [32] and is thought to be a marker for IFN-dominated responses [33]. Negrao-Correa [36] investigated S. mansoni -infected individuals who were subjected to clinical examination and abdominal ultrasound analysis. Interestingly, an earlier study on S. mansoni has shown that the probability of reinfection increases in proportion with schistosomulae-specific IgG2 levels after therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 secretion is under the genetic control of IFN-γ, is up-regulated in Th1-type inflammatory processes [32] and is thought to be a marker for IFN-dominated responses [33]. Negrao-Correa [36] investigated S. mansoni -infected individuals who were subjected to clinical examination and abdominal ultrasound analysis. Interestingly, an earlier study on S. mansoni has shown that the probability of reinfection increases in proportion with schistosomulae-specific IgG2 levels after therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…The major tool for assessing S. mansoni infection-associated morbidity in older patients is ultrasound [22][23][24][25][26][27][28] using the WHOrecommended Niamey scoring system. 29,30 It includes assessment of expected morbidities such as splenomegaly and left lobe hepatomegaly, as well as successively more pronounced liver ultrasound changes scored as image patterns (IP) A (normal), B ("starry sky," abnormal linear opacities of unclear significance), and C through F (progressive hepatic fibrosis).…”
Section: Introductionmentioning
confidence: 99%
“…IgG4 subtypes in human and IgG1 in mouse are involved in resistance and susceptibility to schistosomiasis [58,59] and thus are of great interest for the diagnosis of helminthic diseases [60].…”
Section: Antibody Subtype Specific Reactionmentioning
confidence: 99%
“…We accordingly attempted to analyze the IgG subtypes raised against these antigens, as well as detecting specific IgE antibody, an important immunoglobulin during helminthic infections, including schistosomiasis [59]. The IgG1 subtype was found to be the dominant IgG response to the recombinant antigens (Fig.…”
Section: Antibody Subtype Specific Reactionmentioning
confidence: 99%